Successful School Leadership: Linking with Learning and Achievement - Shane Silpe; Krishna Bista (Journal of MultiDisciplinary Evaluation)
A review of the book Successful School Leadership: Linking with Learning and Achievement by Christopher Day, Ken Leithwood, Pam Sammons, David Hopkins, Qing Gu, Eleanor Joanne Brown, & Elpida Ahtaridou, published in 2011 by Open University Press.